青少年健康素養：由健康促進觀點建構定義與能力指標 Defining Adolescent Health Literacy and Constructing Its Indicators From a Health Promotion Perspective - 廖梨伶 Li-Ling Liao; 劉潔心 Chieh-Hsing Liu; 施淑芳 Shu-Fang Shih; 鄭其嘉 Chi-Chia Cheng; 張子超 Tzu-Chau Chang (National Taiwan Normal University, 2019)
健康素養對健康狀態、健康不平等、醫療支出、醫療照護可近性、健康資訊的理解及醫療場域中的決定行為皆有重要影響。然而，目前健康素養的相關研究卻仍存在以醫療場域為背景及以成人為對象的問題，因此，本研究旨在以健康促進觀點建構青少年健康素養之定義與能力指標。本研究以國中三年級學生及高中職三年級學生為指標發展之目標對象，為能建立青少年健康生活情境之基礎資料，故訪談青少年及與其生活情境相關之重要他人，共 85 名青少年、23 名家長與 34 名教師，並同步參酌國中與高中職健康教育教學相關能力指標，發展青少年健康素養之定義與能力指標，由八位健康教育相關背景之專家學者及八位資深的健康教育教師，進行兩回合的德懷術後定稿。本研究發展出青少年功能性、互動性及批判性健康素養之定義，並依其定義發展出青少年健康素養能力指標共 56 項；在個別指標部分，適用國中階段之指標 13 項，適用高中職階段之指標 18 項，共用指標部分共 25 項，指標內容共涵蓋10 個健康議題。由於本研究之健康素養定義與能力指標之發展乃依據青少年之真實生活情境，也同步考量國家健康教育課程綱要，故可作為健康素養測量工具發展及教學介入策略之重要參考依據。 Research has demonstrated that health literacy significantly affects health status, health inequality, medical expenses, accessibility of medical care, understanding of health information, and decision-making behavior. However, most studies on the topic of health literacy have focused on adults and are based on a medical perspective. This study proposed a definition of health literacy and an ability indicator for adolescents. The target study population were students in their third year of junior and senior high school. Thirty-four teachers, 23 parents, and 85 adolescents were interviewed to collect data concerning the real-life context of adolescents. The collected data and national health education curriculum guildines were used as a reference to develop health literacy definitions and abilities. Eight health education experts and eight senior teachers were invited to conduct a two-round Delphi survey. Based on the 3 types of adolescent health literacy (functional, interactive, and critical health literacy), this study developed health literacy definitions and 56 abilities (10 for the junior high indicator, 18 for the senior high indicator, and 28 for the junior and senior high indicator) covering 10 issues. The definitions and ability indicators in this study were developed on the basis of real-life adolescent contexts and considered Taiwan's health education guildines. Therefore, the results can serve as a valuable reference for developing health literacy measurement instruments or intervention programs.